Problems concerning assessment of anatomical site of accessory pathway in Wolff-Parkinson-White syndrome. - Spurrell, R A (1975)
Twp patients with type B WPW syndrome and reciprocal tachycardias have been studied using intracardiac electrograms and programmed electrical stimulation of the heart. One patient, who had a right-sided accessory pathway giving the surface electrocardiographic appearances of type B WPW syndrome, was shown to have an additional left-sided accessory pathway as occurs in type A WPW syndrome. This concealed left-sided atrioventricular connexion formed the retrograde pathway during reciprocal tachycardia. In the second patient the appearances of type B WPW syndrome were shown to be caused by an accessory pathway between the atrial septum and the right side of the interventricular septum rather than an accessory pathway in the right atrioventricular groove. The significance of these findings when considering surgical interruption of an accessory atrioventricular conduction pathway is discussed.